Experiences of trauma and psychometric properties of the Life Events Checklist among adults in Uganda - Morawej, Zahra; Misra, Supriya; Ametaj, Amantia A; Stevenson, Anne; Kyebuzibwa, Joseph; Gelaye, Bizu; Akena, Dickens (Public Library of Science, 2024)
Exposure to potentially traumatic events (PTE) is common and increases an individual’s risk of developing post-traumatic stress disorder (PTSD) and other psychiatric disorders. PTEs can be screened with the Life Events Checklist for DSM 5 (LEC-5). However, the psychometric properties of the LEC-5 have never been assessed in Uganda. We aimed to estimate the prevalence of PTEs and evaluate the factor structure of the LEC-5 in a sample of N = 4,479 Ugandan adults between February 2018 –March 2020. We used the phenotyping data from a case-control study (NeuroGAP-Psychosis) in Uganda investigating the genetic and environmental risk factors for psychosis spectrum disorders with 4,479 participants (2,375 cases and 2,104 controls). Prevalence for PTEs was determined for all participants and by case-control status. The factor structure of the LEC-5 was assessed using an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). The overall prevalence of exposure to one or more types of PTEs was 60.5%. Cases reported more frequency of exposure to PTEs than controls (64.2% vs 55.4%; p<0.001). The most frequently endorsed traumatic event was physical assault (22.8%), while exposure to toxic substances was the least endorsed (1.7%). There were several differences among the types of events experienced between cases and controls, including cases reporting more experiences of physical (28.6% vs. 16.2%, p<0.001) and sexual assault (11.5% vs. 5.0%, p<0.001) than controls. The EFA yielded a six-factor model that explained 49.8% of the total variance. The CFA showed that a theoretical seven-factor model based on the South African Stress and Health survey was a better fitting model (CFI = 0.935; TLI = 0.908; RMSEA = 0.026) than the EFA. This study revealed a high prevalence of PTEs among cases and controls, and the LEC-5 was found to have good psychometric properties among Ugandan adults.
Keywords: post-traumatic stress disorder; psychiatric disorders; Ugandan adults